The Welsh in America : letters from the immigrants. - Roberts, Sarah; Conway, Alan, 1920-2003 (North American women's letters and diaries., 1961)
The Welsh formed a small but significant part of the great migration from Europe to the United States during the nineteenth century. In this volume they tell their own story in letters they wrote from America to their families and friends back home. The letters are highly readable, written, for the most part, in vivid and entertaining style which reveals the Welsh as an unusually literate people. The 197 letters are arranged chronologically and geographically, starting with letters that tell of the voyage across the Atlantic. Once in America, the immigrants described their experiences in the farming country of New York, Pennsylvania, Ohio, and some of the other midwestern states. Later, as the frontier moved west, they wrote of their efforts to establish exclusive Welsh settlements on the Great Plains. From the industrial centers there are letters from coal miners and iron and steel workers. The fortune seekers who went to California in the gold rush or to the mines in Colorado are also represented. Still others tell of their search for salvation in the Mormon Zion of Utah. For each chapter or group of letters Mr. Conway has written an introduction giving the general background of the region or period and relating it to the Welsh settlers. Thus the events chronicled and the views expressed in the letters become significant in the history of the times. The majority of the letters were written in Welsh and they appear here in translation. Some were obtained from the files of old newspapers or denominational magazines; others came from the collections of the National Library of Wales or from individuals.